When experts disagree: discourse dynamics in participatory planning - MacCallum, Susan Diana (Curtin University, 2006)
The once dominant view of planning as the discovery of an objective 'public good' has been challenged over the last several decades. Radical uncertainty, social diversity, technological change and popular mistrust of traditional government underlie growing calls for more open and flexible governance processes. In order to reclaim some public legitimacy for their actions, governments and public agencies have responded by creating spaces for stakeholder input to policy making.This thesis is concerned with the often uneasy interaction between stakeholders and bureaucracies in these evolving spaces. Specifically, it focuses on one model of participation that has become fairly standard in Australian planning - the delegation of bureaucratic decisions to 'community-based' committees. The enquiry described in the thesis is grounded in case studies of two such committees, both charged with developing strategic responses to land use conflicts in regional (non-metropolitan) Australia.The analysis proceeds from an institutionalist perspective, treating participatory processes not only as fora to resolve divergent opinions and values, but also as encounters between different 'cultural' frameworks, which continue to be actively constructed throughout. From this perspective, it examines the tensions arising within the case studies between cultural practices - especially between bureaucratic and other ways of working - and the discursive means through which such tensions are, or are not, resolved. It also asks whether these means might represent a form of institutional capacity building.To these ends, the enquiry employs a combination of ethnographic, sociological and linguistic methods in an approach that can broadly be called 'critical discourse analysis'. In particular, it focuses on spoken and written texts - meetings, minutes and planning reports - treating these as the realisation of institutional discourses, with potential to reproduce and/or to reconstruct established values, relations and practices.There are three main findings. First, a traditional bureaucratic rationalism continues to permeate the performance of participatory planning, in constant tension with alternative practices brought to processes by 'stakeholder' participants, which can lead to persistent miscommunication. Second, in spite of this tension, participants can find ways of working together, reaching agreement and making progress even without first resolving underlying differences. Third, committees' newly constructed 'ways of working' represent a very uneven form of institutional capacity building - they are highly context-sensitive and create their own tensions between the needs of the moment and the overall aims of the planning process. As such, they do not translate comfortably to general norms or repertoires for acting; moreover, they may not be reified in such a way as to allow their 'travel' to other planning or governance arenas.